Asian American Identification with African Americans, Latinos, and Whites: The Roles of Discrimination and Self-Identified Skin Tone. Issue 2 (2nd April 2020) - Levchak, Philip J.; Levchak, Charisse C.
ABSTRACT: Using a sample of up to 1, 208 Asian Americans, we examine the effects of skin tone on perceived commonality with African Americans, Latinos, and whites. Overall, we find that Asian Americans are more likely to identify with whites than with African Americans or Latinos. When we account for skin tone, we find that Asian Americans with a medium skin tone experience increased odds of perceiving a commonality with African Americans and Latinos. While we expected the relationship between skin tone and perceived commonality to be mediated by experiences of discrimination, this was not the case. We conclude that Asian Americans occupy a position toward the top of the black-white binary and the oppressive racial hierarchy that exists within the United States. Like previous scholars, we suggest that Asian Americans can use their relative standing to disrupt the oppressive racial hierarchy. However, we recognize that whites, holding a position at the top of the racial hierarchy, must also be responsible for dismantling it.